Teacher Strategies in instilling Multicultural Insight in Terms of P3 Activities on The Theme of Global Diversity - Ahmad Nurfendi Fradana; Nisfullailatul Fitriya; Saskia Azza Nabila; Rizqi Laily Amalia; Trinanti Samdini (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
This study aims to analyze the teacher's strategy in instilling multicultural insights through the Pancasila Student Profile Strengthening Project (P3) activities with the theme of Global Diversity. Descriptive qualitative approach is used to explore the role of teachers in designing, implementing, and evaluating multiculturalism-based learning activities. Data were collected through observation, interviews, and documentation at elementary schools that implement the Merdeka Curriculum. The results showed that teachers' strategies include integrating multicultural values in learning, using collaboration-based methods such as discussions and cultural simulations, and developing inclusive and contextual teaching media. The challenges faced by teachers include limited time, resources, and students' understanding of the concept of global diversity. However, intensive efforts through reflection and strengthening the value of tolerance succeeded in improving students' understanding of the importance of appreciating cultural diversity. This study recommends teacher training and the provision of multicultural-based learning resources as strategic steps to optimize the implementation of P3.